THE CORRELATION AMONG VOCABULARY MASTERY, SELF-EFFICACY AND READING COMPREHENSION TOWARD WRITING ABILITY IN RECOUNT TEXT OF ELEVENTH GRADE STUDENTS OF MAN KRECEK PARE - Indayati, Titik (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 2 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
The paper deals with the correlation among vocabulary mastery, self-efficacy and reading comprehension toward writing ability in recount text. Data were collected from eleventh grade students of MAN Krecek Pare.This research used descriptive quantitative as the research design, while the method was correlation. The obtained data in this research was gotten from test technique and questionarie.The result of the vocabulary mastery test is in good category. It can be proven that the good score is dominated by 53 students from 85 samples, and the percent is 62%, for their studentsâ€™self-efficacy questionarie is dominated by 56 students in good category, the percent is 66%for the result of reading comprehension test is dominated by 48 students in good category, the percent is 56% while writing ability is in fair/average category. It is proven that the result of the writing ability in recount text is dominated by 44 students that gain fair/average scores. The percent is 52%.The correlation method of this research uses regression correlation. The significant and simultaneous correlation value among vocabulary mastery (X 1 ), self-efficacy (X 2 ) and reading comprehension (X 3 ) toward writing ability (Y) in recount text of eleventh grade students of MAN Krecek Pare.Here is found the correlation value is 201.320. Being compared with the â€œFâ€ table, it is higher than â€œFâ€ table value at either 5% or 1% level (2.72<201.320>4.04). It means that there is positive significant and simultaneous correlation among vocabulary mastery, self-efficacy and reading comprehension toward writing ability in recount text of eleventh grade students of MAN Krecek Pare.